Robots to learn statistics and citizenship - Lopes, P. C. (2015)
In this paper we report a small part of a broader study that is being carried out under the first author PhD, whose goal is to understand how the use of technologies, specially robots, helps students to develop statistical literacy, reasoning and thinking and their ability to problem-solving, producing meaning and enhancing learning. We assume as phenomenon under study - learning (of statistics and citizenship). In this paper we will analyse how learning of statistics and citizenship occurred throughout the search of the winner of a robot race.